마들렌 비오네의 작품을 응용한 의상 디자인 개발(제2보) - 전엄지; Jeon Eomji; 김정실; Kim Jung-sil (한국디자인포럼, 2018)
연구배경 본 연구는 인체 본연의 아름다움을 토대로 패턴과 소재에 대한 지식을 접목시켜 '바이어스 재단'이라는 창의적인 개발을 한 마들렌 비오네(Madeleine Vionnet)의 작품을 고찰하고, 패턴 구성에서 나타나는 예술성과 조형적인 요소의 작품 특성을 파악하여 활성화 방안을 제시하는 데 그 목적이 있다. 연구방법 ‘비오네’의 패턴 구성에서 나타나는 예술성과 조형적인 요소를 1930년~ 2017년 작품의 변천과정을 고찰하고 현대 의상디자인에 접목하여 작품을 제작한다. 연구결과 ‘비오네’의 디자인 작품과 연구자의 작품을 통하여 현대패션에 재해석함으로써 시대를 초월하는 바이어스 재단의 기법 활용, 그리고 예술성과 조형적인 요소의 작품 특성을 파악하였다. 결론 작품제작을 통하여 현대패션 연구에 독창적인 아이디어를 제시하고 창의적이고 차별화된 패션 이미지로 응용 가능성을 높인다면 소비자들의 개성과 심미성을 만족시킬 수 있는 고부가가치의 패션 산업으로 성장하는데 필요한 기반을 마련할 수 있을 것이다. Background This study is based on the natural beauty of the human body on the subject of human figure and examines Madeleine Vionnet’s creative works who developed ‘bias cut' integrated on the knowledge of patterns and materials. The purpose of this study is to identify the characteristics of artistic and formative elements that appear in the pattern composition and to suggest ways of activation. Methods The artistic and formative elements appearing in the pattern composition of Vionnet’s works from 1930 to 2017 are examined, which are then applied to the work of modern fashion design. Result Through the reinterpretation of contemporary fashion through my works and Vionnet's design, the characteristics of utilization of Bias cut which is one of the all-time great technique, artwork and formative elements were observed. Conclusion By presenting unique ideas for creative and differentiated fashion images through contemporary fashion researches, foundations for growth as a high value-added fashion industry that can satisfy consumers' individuality and aesthetics is to set foot.